Grounded lossy parallel inductance simulation using voltage differencing buffered amplifier - Roongmuanpha, Natchanai; Pukkalanun, Tattaya; Tangsrirat, Worapong (My University, 2017)
An actively lossy parallel RL-type inductance simulation employing voltage differencing buffered amplifier (VDBA) as an active component is presented. The proposed grounded inductance simulator is realized with a single VDBA, one grounded capacitor and one floating resistor. The equivalent inductance value of the simulator can be adjusted electronically through the transconductance parameter of the VDBA. The effect of the VDBA non-idealities on the realized simulator is analyzed in detail. As an application, active second-order current-mode highpass/bandpass filter is designed using the proposed variable lossy inductance simulator. The PSPICE simulation results using TSMC 0.25-μm CMOS technology demonstrate a close agreement with the theory, and also verify the usefulness of the proposed simulator and its filter design application.
Keywords: electronically tunable; inductance simulator; lossy inductor; Voltage Differencing Buffered Amplifier (VDBA)